Variations of Crest-to-Trough TEC Ratio of the East African Equatorial Anomaly Region - Oryema, Bosco; Jurua, Edward; Ssebiyonga, Nicolausi (International Journal of Astrophysics and Space Science 2016, 2015)
In this paper, Vertical Total Electron Content (VTEC) data derived from dual-frequency GPS measurements obtained at two ground stations were used to study the variability of the equatorial ionization anomaly (EIA). The present study only focuses on analysis of the crest-to-trough TEC ratio (TEC-CTR) in the southern crest region. Data used in this study was obtained for the high solar activity year 2012. MAL2 station (Geomag Lat. -12.4°S, Geomag Long. 111.9°E) was considered for the southern crest region whereas ADIS station (Geomag Lat. 0.2°N, Geomag Long. 110.5°E) was considered for the trough region. Diurnal and seasonal variations as well as the dependency of TEC-CTR on solar activity levels were investigated in the present study. The results showed that the diurnal variation pattern of TEC-CTR is characterized by two remarkable peak values, one occurring in the post-midnight hours around 02: 00-03: 00 UT (05: 00-06: 00 LT) and the second (highest) peak occurred in the post-sunset hours around 18: 00-20: 00 UT (21: 00-23: 00 LT). Seasonal TEC-CTR variations showed a semi-annual variation pattern, with maximum peak values occurring in the equinoctial months. TEC-CTR also revealed an existence of winter anomaly in this region, with higher values of TEC-CTR in the winter solstice than summer solstice. TEC-CTR in the daytime post-noon hours; between 01: 00-04: 00 UT (04: 00-07: 00 LT) does not vary much with the solar activity; however, TEC-CTR in the post-sunset hours; between 16: 00-20: 00 UT (19: 00-23: 00 LT) shows a clear dependence on the solar activity, with its values increasing with solar activity
Keywords: Total Electron Content (TEC); Equatorial Ionization Anomaly (EIA); GPS Measurements; Solar Activity